SOCIALIZATION OF POLITICAL LITERACY IN WELCOMING THE 2024 ELECTION TO NOVICE VOTERS AT THE UNIVERSITY OF MUHAMMADIYAH CIREBON - Retno Widyani; Agus Irfan; Badawi; Wiwi Hartati (Jurnal Abdisci, 2024)
Since the Republic of Indonesia became independent on August 17, 1945, several parliamentary elections have been held in Indonesia. The first elections were held in 1955 to elect the House of Representatives and the Constituent Assembly members. The second election to elect members of the House of Representatives was in 1971. Six elections were held during the 32 years of Suharto's rule (1971-1997). Elections in the reform era in 1999 and 2004 elected the first President. In 2009, 2014, 2019, and now 2024. Political literacy has been socialized by Semester 1 students of the animal husbandry and informatics engineering study program at the University of Muhammadiyah Cirebon. The material presented included the history of elections in the country, campaigns on social media, student perceptions and attitudes towards campaigns, and considerations for making choices. The results of the novice voter community service show that semester one students do not understand the history of elections in the country, not all students are interested in participating in campaigns on social media, and students' perceptions and attitudes towards news on social media are critical and use common sense and are not easily provoked by hoax news.